Perbedaan Sikap Mahasiswa dalam Merawat Pasien Menjelang Ajal di Institusi Keperawatan Umum dan Berciri Agama - A'la, Muhamad Zulfatul; Siswoyo, Siswoyo; Maghfiroh, Rahmawati L. (Jurnal Ilmiah Ners Indonesia, 2023)
Students attitude towards palliative care is essential to improve the quality service for dying patients. Ideally, this positive attitudes must be flexible in interpersonal relationship and build up a direct communication, psycological relationship between patient and family, and considering of taking care of dying patients. This research determined the differences between attitude of nursing students at nursing institution with general nursing curriculum and nursing curriculum of religion in caring for dying patients. This research used stratified random sampling method and cross-sectional design. The data used Frommelt Attitudes towards the Care of the Dying Care Form B of Indonesian version (FATCOD-B-I) quesionnarrie in 102 correspondents. The result of this research showed that there is difference attitudes between nursing students from nursing institution with general nursing curriculum (104,18±7,557) and at nursing institution with curriculum of religion (99,82±8,532) in taking care of dying patients with P=0.008. The factors that affect the result is academic background, level of experience, training education of nursing students. For future to know about other factor of attitude toward caring of dying patient such as age and culture.   Abstrak Sikap mahasiswa dalam perawatan menjelang ajal merupakan hal yang esensial dalam upaya peningkatan kualitas pelayanan menjelang ajal. Idealnya, fleksibel dalam hubungan interpersonal, adanya keinginan untuk menjalin komunikasi terbuka, pemikiran psikologis yang berkaitan dengan pasien dan keluarga, dan menganggap merawat pasien menjelang ajal merupakan hal yang menyenangkan. Penelitian ini bertujuan untuk mengetahui perbedaan sikap mahasiswa dalam merawat pasien menjelang ajal di institusi pendidikan dengan kurikulum keperawatan umum dan kurikulum keperawatan berciri agama di wilayah Jember. Penelitian ini merupakan jenis penelitian deskriptif komparatif dengan desain penelitian Cross Sectional. Pengumpulan data menggunakan kuesioner Frommelt Attitudes towards the Care of the Dying Care Form B of Indonesian version (FATCOD-B-I) dengan 102 responden. Hasil dari penelitian menunjukkan bahwa terdapat perbedaan sikap mahasiswa dari institusi pendidikan dengan kurikulum keperawatan umum (104,18±7,557) dan mahasiswa dari institusi pendidikan dengan kurikulum keperawatan berciri agama (99,82±8,532) dalam merawat pasien menjelang ajal dengan P=0.008. Faktor – faktor yang dapat mempengaruhi yaitu level akademik, pengalaman dalam merawat pasien menjelang ajal, pelatihan perawatan pasien menjelang ajal. Penelitian menyarankan untuk meneliti faktor lain terkait faktor usia dan budaya yang dapat mempengaruhi sikap mahasiswa dalam merawat pasien menjelang ajal. Kata Kunci: Kurikulum, Mahasiswa, Sikap, Perawatan Paliatif